2023
DOI: 10.3390/nu15051212
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phytochemicals and Gut Microbiome in Atherosclerosis in Preclinical Mouse Models

Abstract: Gut microbiome alterations have recently been linked to many chronic conditions including cardiovascular disease (CVD). There is an interplay between diet and the resident gut microbiome, where the food eaten affects populations of certain microbes. This is important, as different microbes are associated with various pathologies, as they can produce compounds that are disease-promoting or disease-protecting. The Western diet negatively affects the host gut microbiome, ultimately resulting in heightened arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 142 publications
0
5
0
Order By: Relevance
“…However, studies in mice examining diet-induced obesity have shown an association between weight gain and increased abundance of Rikenella , a genus in the family Rikenellaceae . The same studies demonstrated that Rikenella was positively associated with levels of TG and LDL, plasma and aortic mRNA levels of inflammatory cytokines IL-1β and IL-6, atherosclerotic lesion in the aortic area, and macrophage infiltration within the lesions ( 26 28 ). These latter findings are consistent with the positive association of Rikenellaceae with markers of inflammation in IF5 including VCAM-1, ICAM-1, and MCP-1 found by this study, indicating that this taxon might be associated with enhanced migration and adhesion of innate (and other) immune cells to the site of inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…However, studies in mice examining diet-induced obesity have shown an association between weight gain and increased abundance of Rikenella , a genus in the family Rikenellaceae . The same studies demonstrated that Rikenella was positively associated with levels of TG and LDL, plasma and aortic mRNA levels of inflammatory cytokines IL-1β and IL-6, atherosclerotic lesion in the aortic area, and macrophage infiltration within the lesions ( 26 28 ). These latter findings are consistent with the positive association of Rikenellaceae with markers of inflammation in IF5 including VCAM-1, ICAM-1, and MCP-1 found by this study, indicating that this taxon might be associated with enhanced migration and adhesion of innate (and other) immune cells to the site of inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…We will briefly discuss the association between trimethylamine N-Oxide and CVD, and focus on other microbial metabolites in this review as illustrated in Figure 5 (156).…”
Section: Role Of Microbial Derived Metabolites and Cvdmentioning
confidence: 99%
“…Apart from the Mediterranean diet, probiotics, prebiotics, and their combination synbiotics might play a unique role in this context. The administration of probiotics, especially next-generation probiotics (NGP), such as Akkermansia muciniphila , has already been suggested to offer beneficial effects [ 73 75 ]. In particular, Akkermansia muciniphila has been documented to decrease the formation of abdominal aortic aneurysm, when administered in a mouse model.…”
Section: The Role Of Dietary Choline In Cardiometabolic Disordersmentioning
confidence: 99%